Method for reducing elution of boron from amorphous refractory and method for manufacturing amorphous refractory

Using carbon and borosilicate glass as antioxidants in monolithic refractories addresses excessive boron elution, allowing effective reuse by preventing carbon oxidation.

JP2024174820AActive Publication Date: 2024-12-17JFE STEEL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024083124
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-05
Filing Date
2024-05-22
Publication Date
2024-12-17
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

Monolithic refractories containing boron carbide as an antioxidant exhibit excessive boron elution upon dismantling, leading to disposal as industrial waste and loss of effective reuse.

Method used

Employing a raw material composition containing carbon and borosilicate glass as antioxidants, with specific blending ratios and particle sizes, to reduce boron elution while preventing carbon oxidation.

Benefits of technology

The method effectively reduces boron elution and prevents carbon oxidation, enabling the reuse of monolithic refractories as road base materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174820000001
    Figure 2024174820000001
  • Figure 2024174820000002
    Figure 2024174820000002
Patent Text Reader

Abstract

To provide a method for reducing elution of boron from an amorphous refractory while preventing oxidation of carbon.SOLUTION: A raw material composition containing carbon and borosilicate glass as an antioxidant are used as raw materials of an amorphous refractory. It is preferable that the amount of the borosilicate glass blended in terms of boron element is, on an external basis, 0.1-1.0 pt.mass based on 100 pts.mass of the raw material composition. It is preferable to adjust the blending amount of the borosilicate glass according to the particle size of the carbon.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for reducing boron elution from a monolithic refractory and a method for producing a monolithic refractory. [Background technology]

[0002] When carbon-containing refractories are exposed to high temperatures, the carbon oxidizes and the properties deteriorate, so antioxidants are generally added to the refractories. As an antioxidant, boron carbide (B4C) is used, particularly in monolithic refractories (Patent Documents 1-2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2000-203953 A [Patent Document 2] JP 2014-152092 A Summary of the Invention [Problem to be solved by the invention]

[0004] When unshaped refractories containing boron carbide as an antioxidant are dismantled after use and the particle size is adjusted, the boron may be eluted in excess of the prescribed amount. In this case, the unshaped refractories must be disposed of as industrial waste after use and cannot be effectively used. Therefore, an object of the present invention is to provide a method for reducing the elution of boron from a monolithic refractory while preventing the oxidation of carbon. [Means for solving the problem]

[0005] As a result of extensive investigations, the present inventors have found that the above object can be achieved by adopting the following configuration, and have completed the present invention. That is, the present invention provides the following [1] to [6]. [1] A method for reducing boron leaching from an unshaped refractory, comprising using a carbon-containing raw material composition as a raw material for the unshaped refractory, and borosilicate glass as an antioxidant. [2] The method for reducing boron elution from an unshaped refractory material according to the above [1], wherein the amount of the borosilicate glass, calculated as boron element, is 0.1 to 1.0 parts by mass, based on 100 parts by mass of the raw material composition. [3] A method for reducing boron leaching from an unshaped refractory material according to [1] or [2] above, comprising adjusting the amount of the borosilicate glass according to the particle size of the carbon. [4] A method for reducing boron leaching from a monolithic refractory material according to any one of [1] to [3] above, wherein the carbon is at least one selected from the group consisting of graphite, carbon black, pitch and coke. [5] The method for reducing boron elution from a monolithic refractory material according to any one of [1] to [4] above, wherein the borosilicate glass has a particle size of 0.1 mm or less. [6] A method for producing a monolithic refractory, comprising the steps of: producing a monolithic refractory from a raw material composition containing carbon and borosilicate glass as an antioxidant as raw materials. Effect of the Invention

[0006] According to the present invention, it is possible to reduce the elution of boron from a monolithic refractory while preventing the oxidation of carbon. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] [Method for reducing boron elution from monolithic refractories] The method for reducing boron elution from a monolithic refractory of this embodiment uses a carbon-containing raw material composition as the raw material for the monolithic refractory, and borosilicate glass as an antioxidant. This embodiment will be described in detail below. The following description also includes a method for producing the monolithic refractory material.

[0008] <Raw material composition> In this embodiment, a raw material composition is used as a raw material for the monolithic refractory material. The raw material composition contains at least carbon.

[0009] "carbon" The carbon is not particularly limited, but suitable examples include at least one type selected from the group consisting of graphite, carbon black, pitch, and coke. Pitch is a resinous (liquid) raw material. The particle size of graphite is, for example, 25 to 500 μm, the particle size of carbon black is, for example, 3 to 500 nm, and the particle size of coke is, for example, 1 to 50 μm. The particle size of carbon (excluding pitch) is the volume-based median diameter (particle size at 50% cumulative value) in the particle size distribution determined by a laser diffraction / scattering method.

[0010] The carbon content in the raw material composition is not particularly limited and is appropriately adjusted depending on the application of the monolithic refractory material, etc. For example, the carbon content is preferably 1 to 20 parts by mass, and more preferably 2 to 15 parts by mass, based on 100 parts by mass of the raw material composition.

[0011] 《Fire-resistant raw materials》 The raw material composition may contain, in addition to carbon, a conventionally known refractory raw material as a raw material for the monolithic refractory. Examples of refractory raw materials include alumina raw materials such as brown alumina, fused alumina, sintered alumina, bauxite, diaspore, alumina shale, and calcined alumina; silica raw materials such as silica stone, silica sand, and amorphous silica (e.g., microsilica, silica flower, fumed silica, and white carbon); silica-alumina raw materials such as rosewood, chamotte, clay, pyrosite, andalusite, sillimanite, kyanite, and mullite; spinel raw materials such as fused spinel and sintered spinel; magnesia raw materials such as magnesia clinker; dolomite raw materials such as dolomite clinker; zirconia raw materials such as fused zirconia; zircon raw materials such as zircon sand; silicon nitride raw materials; aluminum nitride raw materials; and silicon carbide raw materials such as SiC.

[0012] The content of the refractory raw material in the raw material composition is not particularly limited, and is appropriately adjusted depending on the application of the monolithic refractory material, etc. The content of the refractory raw material excluding carbon is preferably 75 to 95 parts by mass, and more preferably 80 to 90 parts by mass, based on 100 parts by mass of the raw material composition.

[0013] Binder The feed composition may further contain a binder. Examples of binders include alumina cement (eg, high alumina cement), hydraulic transition alumina, silicates, and phosphates.

[0014] The content of the binder in the raw material composition is not particularly limited and is appropriately adjusted depending on the application of the monolithic refractory material, etc. The content of the binder is preferably 1 to 6 parts by mass, and more preferably 2 to 4 parts by mass, based on 100 parts by mass of the raw material composition.

[0015] Magnesia As mentioned above, the refractory raw material may be a magnesia raw material. However, when magnesia is used as a raw material for monolithic refractories, a part of it reacts with the water used in the manufacture of the monolithic refractories to produce magnesium hydroxide, which decomposes at high temperatures, making the manufactured monolithic refractories porous and making the carbon in the monolithic refractories susceptible to oxidation. For this reason, the magnesium content in the raw material composition is preferably as low as possible, since this provides a superior effect of preventing the oxidation of carbon (described in detail below). Specifically, the content of magnesia (MgO) is preferably 50 parts by mass or less, more preferably 35 parts by mass or less, even more preferably 20 parts by mass or less, particularly preferably 10 parts by mass or less, and most preferably 5 parts by mass or less, based on 100 parts by mass of the raw material composition.

[0016] <Antioxidants> Boron carbide As mentioned above, boron carbide has been used as an antioxidant for carbon. Boron carbide (B4C) is thought to prevent the oxidation of carbon by the following action.

[0017] First, prior to the oxidation of carbon in the monolithic refractory, the reaction represented by the following formula (1) occurs, producing boron oxide (B2O3). Next, the produced boron oxide (B2O3) reacts with SiO2 in the monolithic refractory, causing the reaction represented by the following formula (2). This produces B2O3-SiO2 glass, which coats the carbon. 4B4C+7O2→2B2O3+4CO2···(1) B2O3+SiO2→B2O3-SiO2···(2)

[0018] At this time, not all of the boron oxide (B2O3) becomes B2O3-SiO2 glass by the reaction represented by the above formula (2). In other words, some of the boron oxide (B2O3) remains unreacted in the monolithic refractory. Furthermore, it is believed that if boron oxide (B2O3) remains in the unshaped refractory after use, more boron will be leached out of the unshaped refractory after use.

[0019] The blending amount of boron carbide (BC) calculated as elemental boron (B) is preferably less than 0.1 parts by mass, more preferably less than 0.01 parts by mass, even more preferably less than 0.001 parts by mass, and particularly preferably 0 parts by mass, per 100 parts by mass of the raw material composition.

[0020] Borosilicate glass Therefore, in this embodiment, borosilicate glass (SiO2-B2O3-Na2O-Al2O3) is used as an antioxidant for carbon instead of boron carbide (B4C). When the monolithic refractory is exposed to high temperatures, the borosilicate glass partially melts and coats the carbon, thereby acting as an antioxidant for the carbon. In this case, since almost no boron oxide (B2O3) is produced, the amount of boron eluted from the monolithic refractory after use is less than when boron carbide (B4C) is used.

[0021] That is, according to this embodiment, it is possible to reduce the elution of boron from the unshaped refractory after use while maintaining the effect of preventing the oxidation of carbon in the unshaped refractory. This allows the unshaped refractory material to be effectively utilized after use, for example as roadbed material.

[0022] In addition, boron has a low melting point, so by using borosilicate glass as an antioxidant, the melting of the antioxidant can be promoted and the antioxidant effect of carbon can be enhanced compared to the case where a glass material that does not contain boron is used as the antioxidant.

[0023] Generally, in borosilicate glass, the B2O3 content is about 11 mass %, and the B content is about 3.4 mass %.

[0024] (Containing amount) From the viewpoint of sufficiently obtaining the effect of preventing the oxidation of carbon, the compounding amount of borosilicate glass in terms of B is, for 100 parts by mass of the raw material composition, externally added, for example, 0.01 part by mass or more, preferably 0.1 part by mass or more, and more preferably 0.3 part by mass or more.

[0025] By the way, the smaller the particle size of carbon, the larger the specific surface area, so the coating amount required to prevent oxidation increases. For example, even if the compounding amounts of two types of carbon a and b with different particle sizes (particle size: a < b) are the same, the coating amount required to prevent oxidation is larger for carbon a with a smaller particle size than for carbon b with a larger particle size. Therefore, in this embodiment, it is preferable to adjust the compounding amount of borosilicate glass according to the particle size of carbon. That is, as the particle size of carbon decreases, it is preferable to increase the compounding amount of borosilicate glass.

[0026] Specifically, for example, when using carbon black as carbon, since the particle size of carbon black is, for example, smaller than that of graphite, the compounding amount of borosilicate glass in terms of B is, for 100 parts by mass of the raw material composition, externally added, and more preferably 0.4 part by mass or more.

[0027] On the other hand, if there is too much borosilicate glass, boron oxide (B2O3) is generated in a certain amount, and boron may be easily eluted from the amorphous refractory after use. In addition, if there is too much borosilicate glass, the Na2O component in the borosilicate glass (SiO2 - B2O3 - Na2O - Al2O3) may lower the heat-resistant temperature of the amorphous refractory and also have an adverse effect on the corrosion resistance. Therefore, the compounding amount of borosilicate glass in terms of B is, for 100 parts by mass of the raw material composition, externally added, preferably 1.0 part by mass or less, and more preferably 0.8 part by mass or less.

[0028] (Particle size) By reducing the particle size of the borosilicate glass, it becomes easier to disperse it in the monolithic refractory material, and the effect of preventing the oxidation of carbon can be enhanced. Specifically, the particle size of the borosilicate glass is preferably 0.1 mm or less.

[0029] When carbon black is used as the carbon, the particle size of the carbon black is smaller than that of, for example, graphite, so it is preferable to make the particle size of the borosilicate glass smaller. Specifically, the particle size of the borosilicate glass is preferably 0.075 mm or less.

[0030] Regarding the particle size of borosilicate glass, for example, "0.1 mm or less" means that the particle passes through a sieve with 0.1 mm openings conforming to JIS Z 8801.

[0031] <Unshaped refractories> The above-mentioned carbon-containing raw material composition and borosilicate glass serving as an antioxidant are used as raw materials to produce a monolithic refractory.

[0032] In the case of a shaped refractory produced by pressure molding, a metal material such as metallic aluminum can be used as an antioxidant. On the other hand, when metallic aluminum is used as an antioxidant in a cast-molded monolithic refractory, the water used in the manufacture of the monolithic refractory reacts with metallic aluminum to generate hydrogen gas, which makes the monolithic refractory porous and makes the carbon in the monolithic refractory more susceptible to oxidation. That is, it is difficult to use metallic materials such as metallic aluminum as an antioxidant in monolithic refractories, and it is preferable that monolithic refractories (raw materials for monolithic refractories) do not contain metallic aluminum. Usable antioxidants are limited to boron carbide and the like.

[0033] The method for producing the monolithic refractory is not particularly limited, and any conventionally known method can be used. For example, to obtain a monolithic refractory, the raw materials of the monolithic refractory are mixed, and then kneaded with appropriate amounts of a dispersant and water, and the resulting kneaded product is placed in a form, cured, and dried. In this case, in order to obtain the above-mentioned effect, it is only necessary to prepare the raw material composition (carbon) and the borosilicate glass as the raw materials of the monolithic refractory and mix them together. As a result, the borosilicate glass is evenly dispersed, so no special treatment is required, and it is very simple. EXAMPLES

[0034] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the examples described below.

[0035] <Invention Examples 1 to 13 and Comparative Examples 1 to 9> Alumina (Al2O3), silicon carbide (SiC), high alumina cement, magnesia (MgO) and carbon were used as raw materials for the monolithic refractory in the amounts shown in Table 1 below to prepare raw material compositions A to G. As the carbon, at least one of graphite (particle size: 50 μm), coke powder (particle size: 20 μm), pitch and carbon black (particle size: 55 nm) was used.

[0036] [Table 1]

[0037] The obtained raw material compositions A to G and an antioxidant were used to produce monolithic refractories. The antioxidants used were boron carbide (B4C), borosilicate glass (particle size: 0.075 mm or less), or metallic aluminum.

[0038] More specifically, the antioxidants shown in Table 2 below were mixed in the amounts shown in Table 2 below (boron carbide (B4C) and borosilicate glass are amounts calculated as B) as outer percentages of the raw material composition, and appropriate amounts of dispersant and water were further added and kneaded to obtain a kneaded product. The obtained kneaded material was poured into a formwork with a diameter of 50 mm and a thickness of 100 mm, and cured at 20°C in an air atmosphere for 24 hours, after which the formwork was removed and the material was dried at 110°C for 24 hours. Thus, a test specimen of an Al2O3-SiC-C-based monolithic refractory was obtained.

[0039] <evaluation> Oxidation thickness The obtained test specimen was placed in an air atmosphere and heated at 1200°C for 12 hours to form a decarburized area. Since the decarburized area changes color from black to gray, the test specimen with the decarburized area formed was cut into slices and the depth of the discoloration from the surface of the test specimen was measured with a vernier caliper, and this was calculated as the oxidation thickness. The smaller the oxidation thickness, the better the effect of preventing carbon oxidation can be evaluated.

[0040] {Amount of boron eluted} To simulate used monolithic refractories, the obtained test specimens were placed in a coke breeze and heated at 1500°C for 3 hours. After heating, the test specimens were crushed to pass through a 2 mm sieve, and the crushed pieces were used to carry out an elution test in accordance with Environment Agency Notification No. 46 to determine the amount of boron eluted (unit: mg / L). The lower the amount of boron eluted, the better the effect of reducing the elution of boron from monolithic refractories.

[0041] [Table 2]

[0042] <Summary of evaluation results> See Table 2 above. In Comparative Example 1, in which no antioxidant was used, the oxidation thickness was very large, with oxidation extending to the center of the test piece, and the carbon oxidation prevention effect was insufficient. Moreover, in Comparative Examples 2 to 8, in which boron carbide (B4C) was used as the antioxidant, the amount of boron eluted was large, and the effect of reducing boron elution was insufficient. Furthermore, in Comparative Example 9, in which metallic aluminum was used as the antioxidant, the oxidation thickness was large and the carbon oxidation prevention effect was insufficient.

[0043] In contrast, in Examples 1 to 13, which used borosilicate glass as the antioxidant, the oxidation thickness was small and the amount of boron eluted was small, and both the carbon oxidation prevention effect and the boron elution reduction effect were good.

[0044] Comparing Examples 1 to 6 in which Raw Material Composition A was used, it was found that as the blending amount of borosilicate glass increased, the oxidation thickness decreased and the carbon oxidation prevention effect tended to be more excellent. On the other hand, as the blending amount of borosilicate glass was decreased, the amount of boron elution was decreased, and a tendency was observed in which the effect of reducing boron elution was more excellent.

[0045] In addition, comparing Examples 4, 7 to 10, and 12 to 13, which differ only in the type of raw material composition used, Examples 4 and 7 to 10, which used raw material compositions A to E not containing magnesia (MgO), tended to have a better carbon oxidation prevention effect than Examples 12 to 13, which used raw material compositions F to G containing magnesia (MgO).

Claims

1. A method for reducing boron elution from a monolithic refractory, comprising using a carbon-containing raw material composition as a raw material for the monolithic refractory, and borosilicate glass as an antioxidant.

2. 2. The method for reducing boron elution from an unshaped refractory material according to claim 1, wherein the amount of the borosilicate glass, calculated as boron element, is 0.1 to 1.0 parts by mass, based on 100 parts by mass of the raw material composition.

3. 3. The method for reducing boron elution from a monolithic refractory material according to claim 1, wherein the amount of borosilicate glass blended is adjusted according to the particle size of the carbon.

4. 3. A method for reducing boron leaching from an unshaped refractory material according to claim 1 or 2, wherein the carbon is at least one selected from the group consisting of graphite, carbon black, pitch and coke.

5. 3. The method for reducing boron elution from a monolithic refractory material according to claim 1, wherein the borosilicate glass has a particle size of 0.1 mm or less.

6. A method for producing a monolithic refractory, comprising the steps of: producing the monolithic refractory using a carbon-containing raw material composition and borosilicate glass as an antioxidant as raw materials;

Citation Information

Patent Citations

  • Magnesia-carbon castable refractory and its applied body

    JP1998158072A

  • Monolithic refractory containing carbon, and wet spraying method therefor

    JP2002362980A

  • Sic for monolithic refractory having excellent corrosion resistance, spalling resistance and dryness, production method therefor, and raw material for the monolithic refractory

    JP2003171184A

  • Alumina-silicon carbide-carbonaceous brick

    JP2015189640A

  • Castable refractory for blast furnace trough metal part

    JP2021050122A